2017
DOI: 10.1177/0271678x17705973
|View full text |Cite
|
Sign up to set email alerts
|

mTOR drives cerebral blood flow and memory deficits in LDLR−/− mice modeling atherosclerosis and vascular cognitive impairment

Abstract: We recently showed that mTOR attenuation blocks progression and abrogates established cognitive deficits in Alzheimer's disease (AD) mouse models. These outcomes were associated with the restoration of cerebral blood flow (CBF) and brain vascular density (BVD) resulting from relief of mTOR inhibition of NO release. Recent reports suggested a role of mTOR in atherosclerosis. Because mTOR drives aging and vascular dysfunction is a universal feature of aging, we hypothesized that mTOR may contribute to brain vasc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 75 publications
6
42
0
Order By: Relevance
“…In aged rats, chronic mTOR inhibition with rapamycin, an intervention that extends lifespan (Wilkinson et al, ), ameliorated mTOR‐dependent decline in learning and memory in aging at least partly through the restoration of cerebrovascular function and synaptic structure. Together with our previous studies, these data indicate that mTOR drives cerebrovascular dysfunction both in normative aging and in age‐associated disease states, including AD and cognitive impairment associated with vascular disease (Halloran et al, ; Jahrling et al, ; Lin et al, , ; Van Skike et al, ) and thereby suggests that brain microvascular dysfunction may link aging to an increased risk of AD. Therefore, mTOR attenuation provides a strategy to preserve synaptic and cerebrovascular function during aging and may help to reduce the risk of AD.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…In aged rats, chronic mTOR inhibition with rapamycin, an intervention that extends lifespan (Wilkinson et al, ), ameliorated mTOR‐dependent decline in learning and memory in aging at least partly through the restoration of cerebrovascular function and synaptic structure. Together with our previous studies, these data indicate that mTOR drives cerebrovascular dysfunction both in normative aging and in age‐associated disease states, including AD and cognitive impairment associated with vascular disease (Halloran et al, ; Jahrling et al, ; Lin et al, , ; Van Skike et al, ) and thereby suggests that brain microvascular dysfunction may link aging to an increased risk of AD. Therefore, mTOR attenuation provides a strategy to preserve synaptic and cerebrovascular function during aging and may help to reduce the risk of AD.…”
Section: Discussionsupporting
confidence: 82%
“…We have previously shown that mTOR inhibition attenuates cognitive dysfunction in aged mice (Halloran et al, ). We and others have also shown that chronic mTOR attenuation with rapamycin can prevent and reverse cognitive and cerebrovascular deficits in several independent mouse models of AD (Lin et al, , ;Van Skike et al, ) and vascular cognitive impairment (Jahrling et al, ), leading to improved cerebrovascular function and preserved cognitive outcomes in these models of age‐related disease. The contribution of mTOR to cerebrovascular deficits is associated with normative aging, though its impact on cognitive outcomes remains unknown.…”
Section: Introductionmentioning
confidence: 60%
See 2 more Smart Citations
“…Mice were feeding in Shaoxing City People's Hospital experimental animal centre. Following adaptation to their environment for 1 week, the LDLR−/− mice were randomized into four dietary groups as follows: mice fed with a standard diet (NC group), mice fed a high‐fat diet (20% fat, 20% sugar and 1.25% cholesterol) (HF group), mice fed a high‐fat diet with FA supplementation (75 ug/kg/d20) (HF + FA group) and mice fed a high‐fat diet with rapamycin (10 mg/kg21) (HF + RAPA group). Folic acid was once‐daily oral gavage for 16 weeks; the control and high‐fat groups received saline by oral gavage.…”
Section: Methodsmentioning
confidence: 99%